2022
DOI: 10.1111/jse.12843
|View full text |Cite
|
Sign up to set email alerts
|

Plastid phylogenomics shed light on intergeneric relationships and spatiotemporal evolutionary history of Melocanninae (Poaceae: Bambusoideae)

Abstract: Melocanninae is sister to other subtribes of Paleotropical woody bamboos with some 90 species mainly concentrated in Asia. However, phylogenetic relationships within the subtribe are poorly known. Here, we filled the gaps in complete plastome data of Melocanninae, reconstructed the phylogeny of Melocanninae, and further estimated divergence time and ancestral distribution range. Our results showed that the two major genera, Cephalostachyum Munro and Schizostachyum Nees, were paraphyletic. Species of Cephalosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Wong (monogeneric) (Soreng et al, 2017). The first‐diverging lineage of the Paleotropical woody bamboos, Melocanninae, has estimated stem and crown dates of 15.72 and 10.02 Ma, different from the crown date of 19.68 Ma (Zhou et al, 2022, this volume). Members of the subtribe share an elongated hollow style and are distributed in tropical southeast Asia and South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Wong (monogeneric) (Soreng et al, 2017). The first‐diverging lineage of the Paleotropical woody bamboos, Melocanninae, has estimated stem and crown dates of 15.72 and 10.02 Ma, different from the crown date of 19.68 Ma (Zhou et al, 2022, this volume). Members of the subtribe share an elongated hollow style and are distributed in tropical southeast Asia and South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have shown that variation in chloroplast genomes provides effective information that can be used to resolve phylogenetic relationships at multiple taxonomy levels, especially in taxonomically complex groups [35,36]. For example, chloroplast genome data had resolved the systematic positions of enigmatic taxa in Saxifragales [37] and shed lights on the intergeneric relationships and spatio-temporal evolutionary history of Melocanninae (Poaceae) [36]. Moreover, the chloroplast genome sequences showed variations at the intraspecies levels, and revealed the genetic difference and diversity of endangered species [38,39] and cultivated species [40,41].…”
mentioning
confidence: 99%
“…Four of the manuscripts in this issue include new dated biogeographical analyses (Gallaher et al, 2022;Peterson et al, 2022b;Soreng et al, 2022a;Zhou et al, 2022); three comprise new phylogenetic analyses with subsequent taxonomic novelties (Da Silva et al, 2022;Peterson et al, 2022aPeterson et al, , 2022c, one is an ecological study investigating functional traits in a clade of savanna/wetland grasses (Arthan et al, 2022), one looked at the current distribution of the grasses over the Australian continent to determine migration directionality (Bryceson & Morgan, 2022), and one is an updated classification of the family primarily based on molecular phylogenetic studies (Soreng et al, 2022).…”
Section: Editorialmentioning
confidence: 99%